Collocational competence as a measure of ESL / EFL competency: a scoping review - Tan, Kim Hua; Nurul Aimi Azmi (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this review is to identify the appropriate strategies or methodologies that can help address those problems related to collocational competence amongst English as a Second Language (ESL) and English as a Foreign Language (EFL) learners. The topic of collocational competence needs to be explored given that having collocational competence would advantage language learners to attain second or foreign language fluency. Collocational competence is in fact a reliable indicator of high language proficiency level. Numerous studies that explored collocational competence found that most learners are still facing difficulties in mastering different types of collocations. This problem seems unending despite major advancements in teaching technologies. Therefore, new and exciting ways of learning and teaching collocations that cater to students’ individual needs and that are useful for teachers should be devised. A scoping review protocol was established for this study. A total of 21 articles from 2010 to 2020 were qualitatively synthesised. Of the 21, nine articles on corpus-based methodology, eight articles on traditional methods of teaching collocations and three articles discussing other relevant learning and teaching strategies that focus on solving the problem of lack of collocational competence were isolated and analysed. The findings suggested that implementing an indirect corpus approach in language classrooms may be the most suitable and practical approach that can cater to almost all levels of proficiency whilst consuming a limited amount of resources. The use of corpora in language classrooms is beneficial as it also offers reliable references for learners to explore and for teachers to adopt and teach.